Pengaruh Burnout dan Komitmen Afektif Terhadap Turnover Intention Karyawan Rumah Sakit YK Madira Palembang - Firmansyah, M. Agung; Roswaty; Lazuarni, Shafiera (Jurnal EMT KITA, 2023)
Human resources at the Hospital are professionals who work to provide health services and are the spearhead of the progress of the Hospital. High job pressure, boredom with routines, and unsatisfactory income lead to low commitment to the organization, besides that it creates boredom (burnout) which can lead to the desire to move to another workplace (turnover intention). This study aims to determine the effect of burnout and affective commitment on employee turnover intention at YK Madira Palembang Hospital. This research is a quantitative descriptive study with a sample of 86 respondents using simple random sampling. Data analysis techniques using the t test and F test and multiple linear regression. The results of the t test for the burnout variable (X1) show that there is a positive and significant effect of burnout on employee turnover intention at YK Madira Palembang Hospital, where the t calculated value for the burnout variable is 6.437 > t table which is 1.988, there is also a negative and significant affective commitment effect on employee turnover intention at YK Madira Palembang Hospital, where the t calculated value for the affective commitment variable is -3.162 > t table (1.988). The calculated results of the analysis of the F test, obtained the calculated F value (23.962) > F table (3.06) indicating that the variables X1 burnout and X2 affective commitment have a positive and significant effect together (simultaneously) on turnover intention at RSIA YK Madira Palembang based on the results of the F test analysis measurement simultaneously. It is hoped that hospitals and management should pay more attention to their employees, especially in terms of setting targets and providing salaries and incentives to provide training, promotion, career advancement with the aim of increasing their commitment to the company to reduce the rate of turnover intention.